Counterfeit Cosmetics Perception Among Muslim Government Servants in Wisma Persekutuan Kota Bharu, Kelantan - Abdullah Thani, Ayu Kamareenna; Amalin Azhari, Nurul Nadhira; Amran, Atiela; Rosely, Nurhidayah; Nik Min, Nik Mohd Faris; Haidar Ishak , Muhammad Ammar (Information Management and Business Review, 2024)
The objective of this study is to determine if there is a notable disparity in the perception among Muslim consumers regarding counterfeit cosmetic items in Wisma Persekutuan Kota Bharu based on their level of religiosity and brand consciousness. A total of 219 questionnaires were gathered from Muslim government servants residing in Wisma Persekutuan, Kota Bharu, Kelantan through the simple random sampling technique, and the data were then subsequently examined using SPSS software. The study’s results indicated a notable correlation between brand consciousness and the impression of Muslim government servants in Wisma Persekutuan Kota Bharu regarding counterfeit cosmetics. Additionally, the results indicated that there is no significant correlation between religiosity in relation to the attitude of Muslim government servants in Wisma Persekutuan Kota Bharu regarding counterfeit cosmetics. This study enhances the existing literature pertaining to the research in the field of Halal cosmetics and offers valuable insights to authorities regarding the perception of counterfeit cosmetic products among Muslim consumers. These findings can assist authorities in improving the regulation of the halal cosmetic industry.